An insight of traditional plasmid curing in Vibrio species - Letchumanan, Vengadesh; Chan, Kok-Gan; Lee, Learn-Han (Frontiers in Microbiology, 2015)
As the causative agent of foodborne related illness, Vibrio species causes a huge impact on the public health and management. Vibrio species is often associated with seafood as the latter plays a role as a vehicle to transmit bacterial infections. Hence, antibiotics are used not to promote growth but rather to prevent and treat bacterial infections. The extensive use of antibiotics in the aquaculture industry and environment has led to the emerging of antibiotic resistant strains. This phenomenon has triggered an alarming public health concern due to the increase number of pathogenic Vibrio strains that are resistant to clinically used antibiotics and is found in the environment. Antibiotic resistance and the genes location in the strains can be detected through plasmid curing assay. The results derived from plasmid curing assay is fast, cost effective, sufficient in providing insights and influence the antibiotic management policies in the aquaculture industry. This presentation aims in discussing and providing insights on various curing agents in Vibrio species. To our best of knowledge, this is a first review written discussing on plasmid curing in Vibrio species.